ANALISIS KANDUNGAN PROTEIN KASAR DAN SERAT KASAR PADA LIMBAH SAYURAN PASAR (KOL, SAWI, KULIT JAGUNG) DENGAN PENAMBAHAN EM4 SEBAGAI PAKAN ALTERNATIF: Analysis of Crude Protein and Crude fiber Content in Market Vegetable Waste (Cabbage, Mustard, Corn Skin) with the Addition of EM4 as Alternative Feed) - sri Muliani; Anie Asriany; nancy Lahay (Buletin Nutrisi dan Makanan Ternak, 2022)
Vegetable waste can be used as ruminant animal feed because it is abundantly available and has economic value, the price is cheap and does not compete with human needs, besides that it can reduce environmental pollution. The purpose of this study was to determine the content of crude protein and crude fiber in market vegetable waste as an alternative feed with the addition of EM4. This study used a completely randomized design (CRD) method which consisted of 4 treatments and 3 replications. The results of this study were the addition of EM4 and molasses gave a very significant effect (P<0.01) on the crude protein content of vegetable waste (cabbage, mustard greens, corn husks). The highest protein content was in treatment P0 and P1 with an average value of 19.28 and the lowest crude protein content was found in treatment P2, namely 17.19 and P3 with a value of 17.73, while the effect was not significant (P<0, 05) on the crude fiber content of vegetable waste (cabbage, mustard greens, corn husks) with the addition of EM4 and molasses with the lowest average value at P0 of 18.72 and the highest average value of P2 being 21.26. Based on the results of the study, it can be concluded that the addition of 10% EM4 and molasses in market vegetable waste (cabbage, mustard greens, corn husks) can reduce crude protein content and increase crude fiber.